Ecological Studies on the Grasslands of Jhansi,U. P. - Shankarnarayan, K A; Dabadghao, P M (Annals of Arid Zone, 2016)
This paper deals with the ecological investigation of the natural grasslands at Jhansi. Nine communities have been recognized as a result of this study. Analytic characters in these nine communities have been described. It has been observed that the pattern of. distribution of these communities is largely determined by soil moisture as influenced by. soil depth and texture.In seeking for floristic affinities among the communities at least seven species are common to almost all the communities. These communities are dynamic because of the continual operation of -both progressive and retrogressive forces aided by anthropocentric factors.